A comprehensive prospective analysis of surgical outcomes and adverse events in spinal procedures among octogenarians: a detailed analysis from a German tertiary center - Lenga, Pavlina; Dao Trong, Huy Philip; Papakonstantinou, Vassilios; Unterberg, Andreas; Ishak, Basem (Global spine journal, 2025)
Study design - Prospective case series. - Objectives - Drawing from prospective data, this study delves into the frequency and nature of adverse events (AEs) following spinal surgery specifically in octogenarians, shedding light on the challenges and implications of treating this specific cohort as well as on risk factors for their occurrence. - Methods - Octogenarians who received spinal surgery and were discharged between January 2019 and December 2022 were proactively included in our study. An AE was characterized as any incident transpiring within the initial 30 days after surgery that led to an unfavorable outcome. - Results - From January 2020 to December 2022, 184 octogenarian patients (average age: 83.1 ± 2.8 years) underwent spinal surgeries. Of these, 81.5% were elective and 18.5% were emergencies, with 69.0% addressing degenerative pathologies. Using the Charlson Comorbidity Index, the mean score was 8.1 ± 2.2, highlighting cardiac diseases as predominant. Surgical details show 71.2% had decompression, with 28.8% receiving instrumentation. AEs included wound infections 3.1% for degenerative, 13.3% for tumor and dural leaks. The overall incidence of dural leaks was found to be 2.7% (5/184 cases), and each case underwent surgical revision. Pulmonary embolism resulted in two fatalities post-trauma. Wound infections (26.7%) were prevalent in infected spine cases. Significant AE risk factors were comorbidities, extended surgery durations, and instrumentation procedures. - Conclusions - In octogenarian spinal surgeries, AEs occurred in 15.8% of cases, influenced by comorbidities and surgical complexities. The 2.2% mortality rate wasn’t linked to surgeries. Accurate documentation remains crucial for assessing outcomes in this age group.